The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fmats.2019.00197
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of NO2 Sensing Properties in Pd Functionalized Reduced Graphene Oxides by Electron-Beam Irradiation

Abstract: Herein, we present the effect of electron-beam irradiation (EBI) on the gas-sensing properties of Pd-functionalized reduced graphene oxide (RGO). Scanning electron microscopy, transmission electron microscopy, and X-ray photoelectron spectroscopy were used to characterize the synthesized products. The samples were irradiated using electron beams at doses of 0 (Pd-RGO-0), 100 (Pd-RGO-100), and 500 kGy (Pd-RGO-500), and the NO2 gas-sensing properties were investigated. It was found that irradiation by electron b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 60 publications
2
5
0
Order By: Relevance
“…The mechanism of increasing resistance in the presence of NH 3 gas is explained as follows: rGO and hybridized AuNPs with rGO sensing layers have p-type characteristics wherein holes act as the majority carriers. The electron donor effect of NH 3 gas molecules (reducing agent) will deplete the hole concentration in sensing layers upon adsorption which leads to an increase in resistance of sensor devices [1,4,6,10], [19,20]. Our results are comparable to the report of Sivalingam and Balasubramanian who used rGO/Au hybrid nanostructure for detecting 10,000 ppm of NH 3 gas at RT with the highest sensitivity of 10% [5].…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The mechanism of increasing resistance in the presence of NH 3 gas is explained as follows: rGO and hybridized AuNPs with rGO sensing layers have p-type characteristics wherein holes act as the majority carriers. The electron donor effect of NH 3 gas molecules (reducing agent) will deplete the hole concentration in sensing layers upon adsorption which leads to an increase in resistance of sensor devices [1,4,6,10], [19,20]. Our results are comparable to the report of Sivalingam and Balasubramanian who used rGO/Au hybrid nanostructure for detecting 10,000 ppm of NH 3 gas at RT with the highest sensitivity of 10% [5].…”
Section: Resultssupporting
confidence: 77%
“…Meanwhile, Sivalingam and Balasubramanian use the coreduction method of these precursors (at 80°C for 5 minutes) to synthesize rGO/Au film which was applied to NH 3 sensing at RT [4,5]. Choi et al synthesize rGO and then deposit the Pd layer on the rGO surface by a sputtering process and thermal annealing; a NO 2 gas sensor at RT was made from this Pd-rGO hybrid [6]. From these reports, it can be seen that the mechanism and performance of the sensor depend strongly on the metal used and the synthesis method.…”
Section: Introductionmentioning
confidence: 99%
“…2 MeV EB provokes oxygen functional group adsorption and non oxygen defects in reduced grapheneoxide which is mainly responsible for improved responsivity. Similar phenomena have also been observed in case of Pd functionalized reduced grapheme oxide based gas sensor [64]. In spite of having huge potential of high energy EB as a tool to modify the chemiresistive gas sensing of CPs, researcher community has paid fewer attention on it for both pure CPs and its hybrid nanomaterials.…”
Section: Chemiresistive Gas Sensingsupporting
confidence: 67%
“…The phenomena are responsible for doping through oxidation of organic molecules which improves electrical conductivity and overall device sensitivity in case of detectors like gas sensors [64].…”
Section: Influence Of Atmospheric Oxygenmentioning
confidence: 99%
“…Thus, non-oxygenated defects played an important role in improving the sensing performance. Choi et al [ 130 ] reported the effect of e-beam irradiation (0, 100, and 500 kGy) on the NO 2 -sensing features of Pd-functionalized rGO. The response of the unirradiated sensor and the sensor irradiated at doses of 100 and 500 kGy to 10 ppm NO 2 were 1.027, 1.045, and 1.047, respectively.…”
Section: Irradiated Gas Sensorsmentioning
confidence: 99%